Examining the miniatures of the Gospel № 3756 of Matenadaran after Mesrop Mashtots′ - Matevosyan, Monte (History and Culture, 2025)
When studying the history of Armenian miniature, it becomes clear that the number of manuscripts that have reached us from the 12th century is relatively less. As in the case of handwritten manuscripts created in other centuries, among the manuscripts created in the 12th century, the Gospels make up a significant number. The original M 3756 belongs to the series of Gospels that have come down to us. It does not have a written date, the place of written is also unknown, the writer is "Hovhannes". The original does not have a scenes of the Life of Christ, but it is distinguished by the images of Ammonius of Alexandria and the evangelists, and the variety of khoran (canon tables) and marginal decorations. The image of Ammonius of Alexandria, the author of the Ammonian tablets, gives this manuscript its own uniqueness, because the matenadaranian miniature is the unique example found in the Gospels in the history of Armenian miniatures, which we know. The painter showed his unique style while depicting the Evangelists. Through khoran (canon table) ornaments and title pages, it is possible to follow the development of decorated headpiece of khoran and marginal ornaments. The study of the miniatures allows us to conclude that the painter was familiar with the former Armenian Greater (Mets Hayk′) school of miniatures, also it is not excluded either directly or indirectly with the Byzantine Ottonian book art. Through the miniatures of this manuscript, it is possible to see the trends and characteristic features of the development of the Armenian miniature art of the 12th century.